Iraq : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses Iraq's request for Stand-By Arrangement for 15 months from December 2005 through March 2007, which they intend to treat as precautionary. The authorities' policies have succeeded in promoting overall macroeconomic stability despite the extremely difficult security environment. Economic growth in 2005 is estimated at 2.6 percent, following the rebound of almost 50 percent recorded in 2004. Inflation pressures have moderated in 2005, though prices remain volatile. The medium-term outlook for Iraq is favorable, but subject to many risks.